2006
DOI: 10.1029/2006gl025800
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of primary production and changing of nutrient ratio in the East China Sea: Effect of the Three Gorges Dam?

Abstract: It has been documented that the global proliferation of dam construction on the major river has reduced nutrient and sediment loading to coastal environments. As a consequence, dams can impact marine ecological systems by changing nutrient concentrations and ratios in the coastal zone. From 1998–2004, we conducted a high resolution oceanographic investigation of the East China Sea (ECS) before and after the first filling phase (June 2003) of the Three‐Gorges Dam (TGD). We found that the Si:N ratio in the River… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
147
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(156 citation statements)
references
References 20 publications
5
147
0
2
Order By: Relevance
“…However, the distribution of lower SSS near multiple leading edges of the CDW plume extension did not always correspond to high Chl a. In other words, this result (i.e., low Chl a in the low SSS CDW plume) implies that the presence of terrestrial CDOM within the CDW can lead to overestimation of satellite-derived Chl a values, as suggested by previous studies (e.g., Gong et al 2006). …”
Section: Satellite-derived Acdom Datamentioning
confidence: 49%
See 1 more Smart Citation
“…However, the distribution of lower SSS near multiple leading edges of the CDW plume extension did not always correspond to high Chl a. In other words, this result (i.e., low Chl a in the low SSS CDW plume) implies that the presence of terrestrial CDOM within the CDW can lead to overestimation of satellite-derived Chl a values, as suggested by previous studies (e.g., Gong et al 2006). …”
Section: Satellite-derived Acdom Datamentioning
confidence: 49%
“…Prior to the work reported herein, the principal satellitederived observations of the CDW were based on chlorophyll concentration (Kiyomoto et al 2001;Yuan et al 2005;Gong et al 2006;Kim et al 2009;Shi and Wang 2012). These studies showed that the CDW has profound effects on the physical and biological processes that occur on the ECS shelf.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of dams on land-sea river transport and the related effects on the coastal zones have been reported in many areas around the world adjacent to dammed drainage basins (Humborg et al, 1997;Gong et al, 2006;Schöne et al, 2006). Additionally, some studies have focussed on the trapping efficiency of reservoirs and the effects on hydrograph, sediment and nutrient transport as well as the overall ecological conditions of the dammed watersheds (Friedl and Wüest, 2002;Gubiani et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…According to Gong et al (2006), the primary production off the CRE, as high as 2 079 mg/(m 3 ·d), was induced mostly by riverine nutrient input. NO − 3 concentration off the CRE, in average of 17.6 μmol/L in 2003-2006, was about 1.5-fold of that in the 1980s .…”
Section: Introductionmentioning
confidence: 99%